Multifractal analysis of human canine teeth at nano scale: atomic force microscopy studies - Solaymani, Shahram; Ţălu, Ştefan; Ghoranneviss, Mahmood; Elahi, Seyed Mohammad; Shafiekhani, Azizollah; Hantehzadeh, Mohammadreza; Nezafat, Negin Beryani (International nano letters, 2020)
The aim of the present study is to explore the 3-D micromorphology of human canine teeth materials using multifractal analysis through atomic force microscopy (AFM). The 3-D surfaces of ten extracted canine teeth of a group of 40 year old men were studied (enamel, inter enamel, inter dentin, and cementum) by AFM images in tapping mode and on square areas of 1 μm × 1 μm (512 × 512 points). The AFM images and surface multifractal analysis confirm the dependency of surface micromorphology to their structure–property of these materials across the length scales of the teeth structural architecture. Surface statistical parameters and hence, multifractal approach have been considered as reliable and sensitive tools for quantifying the 3-D surface microtexture changes of human canine teeth materials. The surface of inter dentin had the most irregular topography (the width spectrum Δ α = 2.8361, value bigger than all the other Δ α sample values), while the most regular topography (the width spectrum Δ α = 2.6804, value lower than all the other sample values) was found in cementum. It has been concluded that multifractal analyses can be used as mathematical tools to explore the 3-D micromorphology of human canine teeth materials.